Pengaruh Lingkungan Kerja Dan Disiplin Kerja Terhadap Produktivitas Karyawan Untuk Mendukung Keberlanjutan PT. Prabu Mitra Teknik: The Influence of Work Environment and Work Discipline on Employee Productivity to Support the Sustainability of PT. Prabu Mitra Teknik - Putra, Syafihadi Baiki; Lestari, Tri (CV Warnak Johanna Nusantara, 2025)
This study aims to determine the influence of the work environment and work discipline on employee productivity at PT Prabu Mitra Teknik. This study uses an associative quantitative approach with 55 employees as respondents. Data were collected through questionnaires and analyzed using multiple linear regression tests with the help of SPSS version 23 software. The results of the analysis show that partially, the work environment does not have a significant effect on employee productivity. This is indicated by the t-count value of 1.539 < t-table 2.007 and a significance value of 0.130 > 0.05. On the other hand, work discipline has a positive and significant effect on employee productivity, with a t-count value of 5.450> t-table 2.007 and a significance value of 0.000 <0.05. Meanwhile, simultaneously, the work environment and work discipline together have a significant effect on employee productivity. This is supported by the Fcount value of 25.180 > Ftable 3.17 and a significance of 0.000 < 0.05. Thus, it can be concluded that work discipline is a dominant factor in increasing employee productivity, while the work environment has not shown a significant influence partially. Therefore, companies are advised to focus more on strengthening the culture of discipline and continue to evaluate the conditions of the work environment in order to create optimal synergy in supporting productivity.